Cluster analysis of antiphospholipid antibodies-associated adverse pregnancy outcome patients: based on a 13-years cohort study - Long, Yin; Huang, Can; Cui, Yixin; Xie, Zhijuan; Zhou, Yangzhong; Shi, Xiaohua; Song, Yijun; Tian, Xinping; Li, Mengtao; Liu, Juntao; Liu, Xinyan; Zeng, Xiaofeng; et al. (Clinical and experimental medicine, 2023)
Antiphospholipid antibodies (aPLs) are the leading causes of adverse pregnancy outcomes (APOs). We conducted cluster analysis to identify distinct phenotypes among aPLs-associated APOs patients. This approach aims to facilitate risk stratification and improve pregnancy outcomes for obstetric APS. This was a retrospective study of persistent aPLs positive women cohort in Peking Union Medical College Hospital. Baseline demographic characteristics, clinical manifestation, previous APOs and antibodies profiles were included for hierarchical cluster analysis. Placentae from portions of patients were collected and performed the histopathologic diagnoses. Four clusters among 209 patients with 477 pregnancies were identified. Cluster 1 comprised patients with triple aPLs positivity and demonstrates a high incidence of gestational hypertension (34.92%, P < 0.05) and preterm delivery (20.63%, P < 0.05). Patients in cluster 2 were characterized by lupus anticoagulant (LA) positivity, with high risk of whole gestational APOs. Cluster 3 included patients with isolated aPLs-IgM isotype combined with early miscarriage (60.92%, P = 0.016). Patients in cluster 4 majorly presented aPLs-IgG isotype combined with placenta insufficiency (22.73%). During the follow-up, the live birth rate in cluster 1 and 2 was only 69.20%. Placenta pathology revealed the most severe impairment within cluster 1, whereas clusters 3 and 4 exhibited relatively milder damage. By cluster analysis, we identified four clinical subtypes of aPLs-associated APOs patients. Patients with triple antibodies or high-risk lupus characteristics were prone to occurred gestational hypertension and premature delivery. Isolated LA or aCL/aβ2GPI positivity were found to be more frequently associated with early-stage fetal loss.